1991
DOI: 10.1088/0268-1242/6/11/007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the hole concentration and mobility of p-GaP by Hall and by Raman measurements

Abstract: Larger hole concentrations and lower mobilities are measured by Raman scattering of p-GaP in comparison with results of Hall and conductivity investigations. The Hall factor which is responsible for the differences can be obtained bv these measurements and is discussed on the basis of a two-band model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…For the upper part of the NW, we can obtain more reliable fitting because the L+ peak is spectrally isolated. It should be also noted that even a small inhomogeneity in the form of an axial or radial gradient of n in the volume probed in the Raman experiment will also lead to an overestimation of µ while not having significant effect on the resulting value of n. It has been shown also for p-type and ntype thin-film samples that while the Raman method produces accurate results for n in comparison to Hall data the values of μ tend to be less consistent due to different scattering mechanisms [51,52]. Consequently, we will take the results of the carrier concentration as the important output of the Raman experiments and conclude that a gradient in the carrier concentration is evident along the NW axis, as shown in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…For the upper part of the NW, we can obtain more reliable fitting because the L+ peak is spectrally isolated. It should be also noted that even a small inhomogeneity in the form of an axial or radial gradient of n in the volume probed in the Raman experiment will also lead to an overestimation of µ while not having significant effect on the resulting value of n. It has been shown also for p-type and ntype thin-film samples that while the Raman method produces accurate results for n in comparison to Hall data the values of μ tend to be less consistent due to different scattering mechanisms [51,52]. Consequently, we will take the results of the carrier concentration as the important output of the Raman experiments and conclude that a gradient in the carrier concentration is evident along the NW axis, as shown in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…where C is the (dimensionless) Faust-Henry coefficient. For coupled phonon-hole plasmon systems, ε(ω) can be described by 55 ( )…”
Section: B Raman Spectroscopic Measurements 1 P-type Gasb Raman Spementioning
confidence: 99%
“…χ intra (ω) is composed of contributions from the light and heavy hole intra-valence band transitions and can be expressed as:55 is the respective hole plasmon damping parameter and i p ω is the respective hole plasma frequency. Equation (10) can be simplified by employing an average hole optical effective massEq.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] A number of papers reported that there was a reasonable agreement between the spectroscopic and electrical measurements. However, the carrier mobility obtained from the spectroscopic techniques was occasionally smaller than those obtained from the electrical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…However, the carrier mobility obtained from the spectroscopic techniques was occasionally smaller than those obtained from the electrical measurements. 2,4,5,12,14,15 This discrepancy may arise from the following causes: ͑i͒ For the determination of the drift mobility of the carriers, the Hall factor correction is required. However, this correction has often been neglected, because of the lack of information of the Hall factor, which depends on the temperature and the impurity concentration.…”
Section: Introductionmentioning
confidence: 99%